2022
DOI: 10.3390/antibiotics11020134
|View full text |Cite
|
Sign up to set email alerts
|

Groin Surgical Site Infection in Vascular Surgery: Systemic Review on Peri-Operative Antibiotic Prophylaxis

Abstract: Objectives: Surgical site infections (SSIs) in lower extremity vascular surgeries, post-groin incision, are not only common complications and significant contributors to patient mortality and morbidity, but also major financial burdens on healthcare systems and patients. In spite of recent advances in pre- and post-operative care, SSI rates in the vascular surgery field remain significant. However, compliant antibiotic therapy can successfully reduce the SSI incidence pre- and post-surgery. Methods: In October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…at preventing SSI after various types of vascular surgery (Table 2). Two of these studies also similarly reported that preincision antibiotics and iNPWT reduce the risk of SSI 51–55 . Another also reported that the use of subcuticular sutures instead of staples reduced the risk of SSI after vascular surgery requiring a groin incision 55 .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…at preventing SSI after various types of vascular surgery (Table 2). Two of these studies also similarly reported that preincision antibiotics and iNPWT reduce the risk of SSI 51–55 . Another also reported that the use of subcuticular sutures instead of staples reduced the risk of SSI after vascular surgery requiring a groin incision 55 .…”
Section: Discussionmentioning
confidence: 90%
“…Two of these studies also similarly reported that preincision antibiotics and iNPWT reduce the risk of SSI. [51][52][53][54][55] Another also reported that the use of subcuticular sutures instead of staples reduced the risk of SSI after vascular surgery requiring a groin incision. 55 These systematic reviews did not examine all strategies intended to prevent SSI after lower limb revascularization surgery and variably used Grading of Recommendations, Assessment, Development, and Evaluation to assess certainty.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations